KONFLIK DAN NEGOSIASI DI DALAM PERSPEKTIF: ARSITEKTUR, SOSIOLOGI, TEKNOLOGI DAN KOMUNIKASI - Isnaini, Santi (Universitas Bunda Mulia, 2018)
This article will provide a study of the concepts of conflict and negotiation in various scientificperspectives, which in this context will be seen from the perspective of architecture, sociology, technologyand communication. Each perspective has its own perspective in defining and operationalizing a conceptof conflict and negotiation, since each formal object of the scientific study has different ontologicalorigins. For this reason through this article will be a basic topic development from various angles ofscientific theories that will give a picture of the tradition of each of the scholars. For this reason, acomprehensive discussion of theoretical approaches to the basic topics of conflict and negotiation isrequired. So in this article the discussion will be divided into two big skeletons. The first will discuss thestudy of each discipline and its relation to communication. From several perspectives of architecture,sociology, and technology will be presented one by one epistemologis and study. Then from eachperspective linked red thread with the tradition of communication science. The second major frameworkwill address topics of conflict and negotiation from the various angles of the scholarship. After theprevious discussion has been presented scientific approach, then will be dissected one by one how thescientific approach sees conflict and negotiation. Not only defining the concept of conflict andnegotiation, the discussion will also link between each scientific perspective in conflict resolution throughnegotiation methods. Along with that will be described examples of cases that can clearly illustrate theuse of conflict and negotiation topics in various scientific perspectives.Keywords: Conflict, Negotiation, Architecture, Sociology, Techonology, Communication